1977
DOI: 10.1021/j100520a024
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen penetration into the bulk of palladium

Abstract: The interaction of 02 with polycrystalline Pd was investigated; above 250 °C a significant amount of oxygen is incorporated into the bulk at pressures far below the dissociation pressure of PdO. The rate of uptake into previously unexposed Pd foil was pressure independent, suggesting (1) that penetration into the bulk occurred from an oxygen-saturated surface and (2) that the rate was limited by the process in which chemisorbed oxygen moved out of the surface layer toward the interior of the Pd. The temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Considering the palladium-oxygen system, many investigations have been carried out dealing with the surface adsorption/desorption behaviour of oxygen at low temperatures. Information on the behaviour of oxygen in the bulk of palladium at high temperatures, however, is limited, in part questionable and/or contradictory [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the palladium-oxygen system, many investigations have been carried out dealing with the surface adsorption/desorption behaviour of oxygen at low temperatures. Information on the behaviour of oxygen in the bulk of palladium at high temperatures, however, is limited, in part questionable and/or contradictory [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, only few studies are found that yield statements or data on the solid solubility of oxygen in palladium [1][2][3][4]. Early results stem from gravimetric investigations of the interaction of oxygen with palladium including the oxidation of the metal [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the chemisorption of oxygen on the platinum surface, the oxygen atoms are able to diffuse into the platinum lattice. Dissolution of oxygen in the upper layers of metal atoms was also observed in the case of Pd catalysts (31,32), even when conditions under which palladium oxide is unstable were used (33). By the interaction of the platinum lattice and oxygen atoms a solid phase which is unable to catalyze the desired oxidation of sodium-D-gluconate is formed.…”
Section: Mechanism Of Deactivationmentioning
confidence: 90%
“…The dissociation of active surface species of palladium oxide into less active palladium crystals at 900 OC (Farrauto et al 1992;McCarty, Wong and Chang 1993) The absorption of oxygen by palladium, which impairs the catalytic properties of the metal (Campbell, Foyt and White 1977;Ladas, Imbihl and ErtIl989) Signiflcant hysteresis effects in the temperature-dependent formation and dissociation of PdO (Garbowski et al 1994;Briot and Primet 1991;Lieske and Volter 1985;Chen and Ruckenstein 1981) The nonlinear dependence of catalytic activity on catalyst loading and metal particle size (Hicks et al 1990) Metal-support interactions which may alter the catalytic activity (Baldwin and Burch 1990;Baker, Prestridge and McVicker 1984) Variations in reaction sites due to differences in crystalline planes (Wang, Lee and Schmidt 1985;Greenler et al 1985;Corma, Martin and Perez 1983) …”
mentioning
confidence: 99%